Factors related to advanced stages of change in a clinical sample of adolescents. Issue 2 (24th December 2012) - Taylor, Andrew; Zaitsoff, Shannon L.; Paterson, Ashley
<x xml:space="preserve">Abstract</x> Background The purpose of the present study was to examine the factors predicting a greater motivation to change in a clinical sample of adolescents. Method A total of 107 adolescents participated in this research prior to beginning outpatient treatment. Participants completed a modified version of the Motivational Stages of Change for Adolescents Recovering from an ED, the Difficulties in Emotional Regulation Scale and the Behavioral Assessment System for Children–Self‐Report. Results More advanced stages of change were associated with better parent–adolescent relationships and better emotional regulation. Conclusion Incorporating parents in treatment to enhance parent–adolescent relationships and instructing parents in emotional regulation techniques to assist the adolescent may enhance their motivation to recover.